First approximation of a stereochemical rationale for the genetic code based on the topography and physicochemical properties of "cavities" constructed from models of DNA. - Hendry, L B (1981)
To examine the question of whether or not the genetic code has a stereochemical basis, we used artificial constructs of the topography and physicochemical features of unique "cavities" formed by removal of the second codon base in B-DNA. The effects of base changes on the stereochemistry of the cavities are consistent with the pattern of the genetic code. Fits into the cavities of the side chains of the 20 L amino acids involved in protein synthesis can be demonstrated by using conventional physicochemical principles of hydrogen bonding and steric constraints. The specificity of the fits is remarkably consistent with the genetic code.